Context aware routing management architecture for airborne networks. Issue 4 (1st July 2016) - Betances, Addison; Hopkinson, Kenneth Mark; Silvius, Mark
Abstract : Military environments require highly dynamic mobile ad hoc networks (MANETs) to meet operational mission requirements. Decision makers rely on the timely delivery of critical battlefield information to make informed determinations quickly and as accurately as possible. However, traditional MANET routing protocols do not provide quality of service (QoS). Furthermore, they do not implement active controls to minimise the impact of network congestion. This study proposes the use of the information embedded in an air tasking order (ATO) during the planning phase of military missions to optimise the network performance. The trajectories of relevant nodes (airborne platforms) participating in the MANET can be forecasted by parsing key information contained in the ATO. Using this idea it is possible to optimise network routes to minimise edge overutilisation and increase network throughput. In one simulated test case, there was a 25% improvement of network throughput, and 23% reduction on dropped packets. Using this technique, the authors can selectively preserve the QoS by establishing network controls that drop low‐priority packets when necessary. The algorithm improves the overall MANET throughput while minimising the packets dropped due to network congestion.